2016
DOI: 10.1111/ddi.12459
|View full text |Cite
|
Sign up to set email alerts
|

Spatial associations of ecosystem services and biodiversity as a baseline for systematic conservation planning

Abstract: Aim Protected areas are frequently defined on the basis of biological importance. Ecosystem services are expected to be under protection when biodiversity is preserved; however, new approaches are needed to confirm this statement. We evaluated how spatial associations between ecosystem services and plant biodiversity on a large spatial scale influence their representativeness in current protected areas. Location Brazilian seasonally tropical dry forest (Caatinga). Methods We produced woody plant biodiversity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 45 publications
(51 reference statements)
4
30
0
2
Order By: Relevance
“…), as well as at the regional level in tropical (Manhães et al. ), Mediterranean (Vilà et al. ), temperate, and boreal forests (Paquette and Messier ).…”
Section: Introductionmentioning
confidence: 99%
“…), as well as at the regional level in tropical (Manhães et al. ), Mediterranean (Vilà et al. ), temperate, and boreal forests (Paquette and Messier ).…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that conservation planning focusing on biodiversity alone does not guarantee the protection of the full range of provisioning and regulatory ecosystem services, hence these must be factored into SCP approaches (Manhaes et al 2016). IPAs, as a national-based system, may not be sufficiently fine-scale to encompass the undisputed need to conserve plants at all spatial scales and the more local ecosystem services they provide such as pollinator food sources.…”
Section: Consultation On Revised Ipa Selection Criteriamentioning
confidence: 99%
“…Previous studies have suggested a positive relationship between forest productivity and biodiversity at global scales (Liang et al 2016), as well as at the regional level in tropical (Manhães et al 2016), Mediterranean (Vil a et al 2013), temperate, and boreal forests (Paquette and Messier 2011). However, other studies have found weak (Armenteras et al 2015) or even negative relationships (Naidoo et al 2008, Murray et al 2015.…”
Section: Introductionmentioning
confidence: 95%